Letter - Dimmock, W. G.
037-0068-001 COMMUNICATIONS-WRITE ON SEPARATE SHEETS FOR EACH SUBJECT. AMALGAMATED UNION OF BUILDING TRADE WORKERS OF GREAT BRITAIN & IRELAND Approved Society No. 257. Telegrams: "Buildcres, Clapcom, London." Telephone: Macaulay 2442 (3 Lines) District Committee Hants Dis Organiser Secretary's Address 445 Burgess Rd Swaythling Southampton Our Ref. Your Ref. Date July 31st 1937 Sir Walter Citrine Gen Sec. T.U.C. Transport House London S.W.1 Dear Sir & Bro Many thanks for your kindness in forwarding a cheque of £3 -3-0 to me to fund the cost of repairs to my car & for your appreciation of help given toward "Basque Children. Only too pleased to do what I could to assist. I enclose receipt for amount of cheque sent me. Yours Fraternally W.G. Dimmick Hants Dis Organiser 292/946/37/68